Exhibit celebrating 150 years of the student experience at Colorado State University, exhibit case 4 of 4 - McClelland, Deborah Ann, artist; Colorado State University. Archives and Special Collections, author (Colorado State University. Libraries, 2019)
Display items from the fourth of four exhibit cases depicting the student experience at Colorado State University. The exhibit is associated with the university's 150th anniversary celebration in 2020. Focusing on years into the future, included are images of Amy Van Dyken during a 1994 swim meet with Brigham Young University; a student playing cello on the Oval in 2001; students in a computer laboratory at Rockwell Hall in 2002; and members of the Asian/Pacific American Cultural Center at the 2015 Colorado Dragon Boat Festival. A summary is given of digital age developments, the start in 2001 of a diversity symposium, and expansion to three campuses.
Keywords: Colorado State University -- History; sesquicentennial; 150th anniversary; student activities; Van Dyken, Amy; Asian/Pacific American Cultural Center; Exhibitions; Olympics; Cello; Computers; Dragon boat festivals